Bibliometric Analysis: Juvenile Delinquency Trends 2020-2024 - Jazilah, Na’maul; Wafa, Iqbal Ali (CV. Lentera Literasi Indonesia, 2025)
Juvenile delinquency is a confusing problem and is the center of attention throughout the world. Various efforts have been made to prevent and handle juvenile delinquency. This study aims to determine the pattern of collaboration, dynamics of research trends, and dynamics of juvenile delinquency research. Data using the sciencedirect database with the keyword juvenile delinquency. This study uses bibliometric analysis with the help of Vosviewer. The results of the analysis show that juvenile delinquency in sciencedirect contains 812 articles. Discussions related to juvenile delinquency are widely discussed with aggression, meta-analysis, depression, adolescents, neglect, victimization, gender, detention, symptoms, profiles, child abuse, disorders, psychopathy, interviews, drugs, and the justice system. Reduced color density indicates that research on the topic is still limited or rarely conducted. The results of this study indicate that the least studied were ASPD (antisocial personality disorder), BPD (borderline personality disorder), antisociality, psychopathic personality, abusive parenting, maternal depression, judgement, childhood trauma, callous irritability, and aggressive behavior